Ixekizumab: an alternative for HIV-positive psoriasis patients - Fanghua Liu; Zhou Liu; Rongming Yang; Dandan Huang; Yongzhi Han (AIDS Research and Therapy)
Abstract Psoriasis is a recurrent and protracted inflammatory disease. Generalized erythema, plaques, and silvery scales on the surface mainly characterize its skin lesions. Biologics bring new hope to psoriasis patients. However, HIV infection is a major concern before receiving biologics. Here, we present a case of the efficacy and safety of Ixekizumab, an interleukin 17 inhibitor, in the treatment of psoriasis patients living with HIV (PPLHIV).